Ethanol Exposure During the Intravenous Administration of Chemotherapeutic Drugs: An Analysis of Clinical Practice and a Literature Review. Issue 5 (6th May 2022) - Hiver, Quentin; Henry, Héloïse; Vasseur, Michèle; Cuvelier, Elodie; Le Rhun, Émilie; Turpin, Anthony; Décaudin, Bertrand; Odou, Pascal; Simon, Nicolas
Abstract : PURPOSE: Injectable cytotoxics may be formulated with ethanol. This study sought to quantify the amount of ethanol exposure during chemotherapy infusions. MATERIALS AND METHODS: We first reviewed the antineoplastic drugs (Anatomical Therapeutic and Chemical code L01) and oncologic supportive care drugs (eg, antiemetics) currently available in France, to identify preparations containing ethanol. The amount of ethanol in the final chemotherapy preparation was calculated. Next, we performed a 2-year, single-center, retrospective analysis of injectable antineoplastic drug compounding in routine clinical practice in a French university medical center. Finally, we reviewed our results with regard to the literature data. RESULTS: Ten of the 60 cytotoxic products on the market contained ethanol at concentrations of up to 790 mg/mL, depending on the drug, formulation, and supplier. Several final preparations contained more than 3 g of ethanol per infusion (the maximum recommended by the European Medicines Agency); this was notably the case for gemcitabine, paclitaxel (up to 20 g ethanol per injection, for both), and etoposide (up to 50 g ethanol per infusion). The analysis of our compounding activity showed that 3, 172 (4.99%) of the 63, 613 chemotherapy preparations (notably paclitaxel) contained more than 3 g of ethanol. None of the oncologic supportive care drugs contained ethanol. CONCLUSION: Patients are exposed to ethanol during the infusion of antineoplastic drugs. With a view to better patient care, physicians and pharmacists should carefully evaluate the risk of ethanol exposure throughout the course of cytotoxic drug treatment.